Narrative methods for the human sciences - Riessman, Catherine Kohler, 1939- (Los Angeles, Calif. : Sage Publications, 2008)
Aimed at providing the rigour needed to advance narrative analysis, the author provides an explanation and guideline to readers on presentation of and reliance on detailed transcripts of interview excerpts, methods for analysing the structural features of discourse, and more.
Looking back, looking forward -- Constructing narratives for research -- Thematic analysis -- Structural analysis -- Dialogic/performance analysis -- Visual analysis -- Truths and cautions.
Bibliografske bilješke: 225-244
Kazalo